Representasi Tokoh Sri Asih dalam Film dan Komik Sri Asih - Oktaviani, Vini; Setiadi, David; Firdaus, Asep (Universitas Tidar, 2024)
The comic Sri Asih which was produced after the screening of the film Sri Asih, is an innovation in de-ecranization research because de-ecranization tends to focus on changing the vehicle from a film to a novel. The selection of this object was based on the researcher's interest in the character Sri Asih, who is the first female superhero in Indonesia and is no less great than foreign superheroes, as well as to appreciate the new genre of Indonesian cinema that is packaged in the Bumilangit Cinematic Universe. This research aims to describe the characterization of Sri Asih in the film Sri Asih by Upi Avianto and the comic Sri Asih by Rizqi R. Mosmarth and Dody Eka. The research method used is a qualitative descriptive method. This method produces descriptive data originating from personal speech. The intertextuality approach and de-ecranization studies are used to analyze the structure of the film and comic Sri Asih, which focuses on analyzing the plot, setting, characters, and characterization. Meanwhile, the study of de-ecranization serves to add and change variations in the comparison of the two works. The results of the research conducted show that the film and comic Sri Asih both have superhero themes and use a forward plot as a component to form the storyline. Meanwhile, other building elements in the two works are relatively the same. As for the form of transformation from the film Sri Asih into the comic Sri Asih, there are additional variations and changes.